When Disasters Strike: An Interview by Linda Silka with Joyce Rumery and Tom Abbott - Rumery, Joyce; Abbott, Thomas; Silka, Linda (Maine Policy Review, 2013)
Joyce Rumery and Tom Abbott in this interview with Linda Silka describe their experiences when they helped libraries devastated by Hurricane Katrina in New Orleans, and how Maine libraries might prepare for disasters.
Keywords: libraries; disaster planning